Assessing the Effectiveness of Tradable Landuse Rights for Biodiversity Conservation: An Application to Canada's Boreal Mixedwood Forest - Marian Weber (Fondazione Eni Enrico Mattei (FEEM), 2004)
Ecological reserve networks are an important strategy for conserving biodiversity. One approach to selecting reserves is to use optimization algorithms that maximize an ecological objective function subject to a total reserve area constraint. Under this approach, economic factors such as potential land values and tenure arrangements are often ignored. Tradable landuse rights are proposed as an alternative economic mechanism for selecting reserves. Under this approach economic considerations determine the spatial distribution of development and reserves are allocated to sites with the lowest development value, minimizing the cost of the reserve network. The configuration of the reserve network as well as the biodiversity outcome is determined as a residual. However cost savings can be used to increase the total amount of area in reserve and improve biodiversity outcomes. The appropriateness of this approach for regional planning is discussed in light of key uncertainties associated with biodiversity protection. A comparison of biodiversity outcomes and costs under ecological versus economic approaches is undertaken for the Boreal Forest Natural Region of Alberta, Canada. We find a significant increase in total area protected and an increase in species representation under the TLR approach.
Keywords: Q28; Q21; H41; 330; Biodiversity conservation; Reserve design; Tradable landuse rights; Artenvielfalt; Landnutzung; Sachenrecht; Wald; Kanada